Trends in characteristics of fentanyl-related poisonings in the United States, 2015-2021. (4th July 2022) - Palamar, Joseph J.; Cottler, Linda B.; Goldberger, Bruce A.; Severtson, Stevan Geoffrey; Grundy, David J.; Iwanicki, Janetta L.; Ciccarone, Daniel
ABSTRACT: Background: Fentanyl-related deaths continue to increase in the United States; however, most national studies focus on fatal overdose. More research, including data on nonfatal overdose, is needed. Objective: We examined trends in characteristics of fatal and nonfatal fentanyl-related poisonings ("exposures") in the US. Methods: National Poison Control data were examined to estimate trends in characteristics of reported exposures between 2015 and 2021 (N = 15, 391; 38.7% female). We also delineated correlates of experiencing a major adverse effect or death. Results: The proportion of exposures increased among all age groups between ages 13 and 39 (ps < .05) with the largest increase among those age 13–19 (a 127.8% increase). With respect to reasons for use, the proportion of cases involving fentanyl "abuse" increased by 63.8% ( p  < .001). The proportion involving fentanyl inhalation increased 427.6% from 5.7% to 29.9% and injection increased from 6.7% to 9.6%, a 42.3% increase (ps < .01). The proportion also increased for co-use of methamphetamine (by 669.0%), cocaine (by 374.0%), and heroin (by 159.5%). The proportion of major adverse effects increased from 15.5% to 39.6% ( p  < .001). In the multivariable model, "abuse", suspected suicide attempts, and use via inhalation were risk factors for experiencing a major effect or death, and misuse, ingestion, dermal use, and co-use of methamphetamine were associated with lower risk. Conclusion: Poison Control data suggest that characteristics of individuals exposed to fentanyl continue to shift, with use via inhalation increasing and medical outcomes of nonfatal poisonings becoming more severe. These results complement mortality data and inform prevention and harm reduction efforts.